Pre-pregnancy care for women with pre-gestational diabetes mellitus: a systematic review and meta-analysis - Wahabi Hayfaa A; Alzeidan Rasmieh A; Esmaeil Samia A (BMC, 2012)
Abstract Background Pre-gestational diabetes mellitus is associated with increased risk for maternal and fetal adverse outcomes. This systematic review was carried out to evaluate the effectiveness and safety of pre-pregnancy care in improving the rate of congenital malformations and perinatal mortality for women with pre-gestational diabetes mellitus. Methods We searched the following databases, MEDLINE, EMBASE, WEB OF SCIENCE, Cochrane Library, including the CENTRAL register of controlled trials and CINHAL up to December 2011, without language restriction, for any pre-pregnancy care aiming at health promotion, glycemic control and screening and treatment of diabetes complications in women with type I or type II diabetes mellitus. Study design were trials (randomized and non-randomized), cohort and case-control studies. Results Of the 2452 title scanned 54 full papers were retrieved of those 21 studies were included in this review. Twelve cohort studies at low and medium risk of bias, with 3088 women, were included in the meta-analysis. Meta-analysis suggested that pre-pregnancy care is effective in reducing congenital malformation, Risk Ratio (RR) 0.25 (95% CI 0.16-0.37), number needed to treat (NNT) 19 (95% CI 14-24), and perinatal mortality RR 0.34 (95% CI 0.15-0.75), NNT = 46 (95% CI 28-115). Pre-pregnancy care lowers glycosylated hemoglobin A1c (HbA1c) in the first trimester of pregnancy by an average of 1.92% (95% CI −2.05 to −1.79). However women who received pre-pregnancy care were at increased risk of hypoglycemia during the first trimester of pregnancy RR 1.51 (95% CI 1.15-1.99). Conclusion Pre-pregnancy care for women with pre-gestational type 1 or type 2 diabetes mellitus is effective in improving rates of congenital malformations, perinatal mortality and in reducing maternal HbA1C in the first trimester of pregnancy. Pre-pregnancy care might cause maternal hypoglycemia in the first trimester of pregnancy.